Approach To Regulation of Infrastructure - Planning Commission (Planning Commission, 2008)
This paper analyses the current state of regulatory law and the associated institutional framework in India applicable to some of the key infrastructure sectors. There is an uneven approach to regulation across and at times even within different sectors of the economy because the system in each sector has been put in place as policies have evolved at different times. The paper sets out the objectives of regulating infrastructure sectors, and argues the case for establishing an overarching framework in order to eliminate divergent mandates currently prescribed for various sectoral regulators. The need for such an initiative arises because infrastructure development in India is expected to follow a very different path in the years ahead compared to the past, with a much larger role for private investment in one form or other of public-private partnership.
Planning Commission Government of India
Planning Commission Government of India